Excess of Organic Carbon in Mountain Spruce Forest Soils after Bark Beetle Outbreak Altered Microbial N Transformations and Mitigated N-Saturation - Kaňa, Jiří; Tahovská, Karolina; Kopáček, Jiří; Šantrůčková, Hana (PloS one, 2015)
Mountain forests in National park Bohemian Forest (Czech Republic) were affected by bark beetle attack and windthrows in 2004-2008, followed by an extensive tree dieback. We evaluated changes in the biochemistry of the uppermost soil horizons with the emphasis on carbon (C) and nitrogen (N) cycling in a near-natural spruce (Picea abies) mountain forest after the forest dieback, and compared it with an undisturbed control plot of similar age, climate, elevation, deposition, N-saturation level, and land use history. We hypothesised that the high litter input after forest dieback at the disturbed plot and its consequent decomposition might influence the availability of C for microorganisms, and consequently, N transformations in the soil. The concentrations of dissolved organic C (DOC) and N (DON) in soil water extracts rapidly increased at the disturbed plot for 3 yeas and then continually decreased. Net ammonification exhibited a similar trend as DOC and DON, indicating elevated mineralization. Despite the high ammonium concentrations found after the forest dieback (an increase from 0.5 mmol kg-1 to 2-3 mmol kg-1), net nitrification was stable and low during these 3 years. After the DOC depletion and decrease in microbial biomass 5 years after the forest dieback, net nitrification started to rise, and nitrate concentrations increased from 0.2-1 mmol kg-1 to 2-3 mmol kg-1. Our results emphasize the key role of the availability of organic C in microbial N transformations, which probably promoted microbial heterotrophic activity at the expense of slow-growing nitrifiers.
Keywords: dusík; Coleoptera; brouci; uhlík; smrk; Animals; Picea; zvířata; Carbon; Nitrogen